Prototipe Alat Pemantauan Suhu untuk Rantai Dingin Produk Mengunakan Near Field Communication, Studi Kasus Distribusi Darah - Priyandari, Yusuf; Suletra, I Wayan; Mas’ud, Azmi; Pujiharto, Adi Norrochmat (Universitas Muhammadiyah Surakarta, 2017)
Temperature monitoring apparatus is required for the distribution of certain products that are distributed using cold chain method. Temperature gauges that use analog and digital thermometers can not store temperature data in transit. The digital temperature register apparatus (logger) in the market temperature is relatively expensive and does not provide early warning if the temperature in the storage box products out of permitted temperature limits. The research developed a prototype of a temperature monitoring device for the distribution of cold chain products. Case studies on blood distribution are used as a basis for determining the need for temperature monitoring devices. The product prototype is made by stages in accordance with generic product development method. The resulting prototype can provide temperature information in the cold box during the course of blood distribution. The prototype can also provide warnings in the form of sounds and lights when the temperature inside the cold box is outside the ideal temperature limit / permitted for the blood distribution process. Temperature history data during the trip can be stored in NFC Tags. The data can then be read using smart-phone devices that feature NFC.